Values of Physical Education and sports As character development and strengthening - Andi Sahrul Jahrir; Adam, Arlin; Kamaruddin, Syamsu A. (JOURNAL RESPECS (Research Physical Education and Sports), 2024)
world of education that teaches about how to live a healthy life and maintain fitness, but in it there are values that can be used as a driving force for developing and strengthening character, some of the values in sports are referred to in this article. in the form of Fair play, cooperation and teamwork, discipline and independence, leadership and mental toughness, it is hoped that these values can become a reference that can build and strengthen character so that it grows into optimal character both personally and in social life. The research method used is a qualitative method which produces descriptive data using literature studies